Structure of highly substituted agarans from the red seaweeds Laurencia obtusa and Laurencia filiformis - Canelon Gonzalez, Dilsia Josefina (2014)
The water extracts from red seaweeds Laurencia obtusa and Laurencia filiformis comprise complex sulfated agarans. Those from L. obtusa have 3-linked β-d-galactose units in part sulfated on 2-position or methylated on 6-position, while the 4-linked units are mostly 3,6-anhydro-α-l-galactose and α-l-galactose 6-sulfate, some of the latter units are substituted with β-d-xylose on 3-position, precluding alkaline cyclization. The 3-linked β-d-galactose units of the agarans from L. filiformis are mostly sulfated on 2-position, but approximately half of these residues also carry the 4,6-O-(1-carboxyethylidene) group. The 4-linked 3,6-anhydro-α-l-galactose units are methylated or substituted in part with single stubs of β-d-xylose on 2-position. This is the first time that substitution with xylose of 3,6-anhydro-α-l-galactose is reported. Besides, α-l-galactose 2-sulfate carrying single stubs of β-d-xylose on 3-position was also detected. These galactans have some common structural characteristics with those of other species of this genus, but also others that are specific for these species.